OVERVIEW OF THE LEVEL OF DEPRESSION, ANXIETY AND POSTOPERATIVE STRESS IN BONE TUMOR PATIENTS AT ORTHOPEDIC HOSPITAL PROF. DR. R. SOEHARSO SURAKARTA - Didit Triono; Aris Prayitno; Endang Winarni; Sri Mulyati; Nanda Wardhana (Jurnal Health Sains, 2023)
Bone tumors are abnormal cell growths that occur in bones. Although fairly rare, bone tumors are not an easily cured disease, the type of bone tumor that attacks many those aged 10-20 years is classified as an active and aggressive type of tumor. Because once attacked, the roots can gnaw the bone to require amputation, because if not, it will risk the safety of the patient's life. One treatment of bone tumors is surgery. But in the treatment of surgery, it is not uncommon for psychological problems to arise experienced by patients. Psychological problems that often arise when postoperative bone tumors it is depression, anxiety and stress. The purpose of this study was to determine the picture of the level of depression, anxiety and postoperative stress in bone tumor patients. This study used a Quantitative descriptive research design, the sampling technique used in this study was total sampling. The samples in this study were all preoperative bone tumor patients totaling 39 people. The instrument used is DASS. The results showed that respondents did not experience depression, namely as many as 27 people (69.2%), 7 people (17.9%) experienced mild depression and 5 people (12.8%) experienced moderate depression. Respondents with very severe anxiety, namely as many as 13 people (33.3%), then 12 people (30.8%) did not experience anxiety, then moderate anxiety levels, which were as many as 11 people (28.2%), very severe anxiety as many as 10 people (25.6%).